2019
DOI: 10.1186/s12890-019-0963-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between inflammatory bowel disease and chronic obstructive pulmonary disease: a systematic review and meta-analysis

Abstract: IntroductionThere is evidence of an association between inflammatory bowel disease (IBD) and lung conditions such as chronic obstructive pulmonary disease (COPD). This systematic review and meta-analysis explored the risk of new onset IBD in patients with COPD and new onset COPD in IBD patients.MethodsWe performed a systematic review of observational studies exploring the risk of both associations. Two independent reviewers explored the EMBASE, MEDLINE, LILACS and DOAJ databases, and the risk of bias was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…Douglas et al [37] in their study found abnormal PFT in 32% of patients with UC, while Sethy et al [38] and Tzanakis et al [39] found abnormal PFT in 17 and 27% of patients with UC, respectively. Labarca et al [40] in their systemic review and meta-analysis found a relative risk (RR) of 2.02 for a new diagnosis of IBD in the COPD patients. This may be due to negative impact on colonic mucosae resulting in increased proinflammatory cytokines and angiogeneis factor.…”
Section: Discussionmentioning
confidence: 99%
“…Douglas et al [37] in their study found abnormal PFT in 32% of patients with UC, while Sethy et al [38] and Tzanakis et al [39] found abnormal PFT in 17 and 27% of patients with UC, respectively. Labarca et al [40] in their systemic review and meta-analysis found a relative risk (RR) of 2.02 for a new diagnosis of IBD in the COPD patients. This may be due to negative impact on colonic mucosae resulting in increased proinflammatory cytokines and angiogeneis factor.…”
Section: Discussionmentioning
confidence: 99%
“…South Korea has one of the highest incidence rates of IBD among all Asian countries [23,24,25,26]. Recent large-scale and scientifically robust studies regarding the aforementioned association, conducted in Asia, report findings comparable to regions with a high incidence of IBD such as Europe and Canada [7,16,27]. It is imperative to be up to date about the gastrointestinal symptoms suggestive of IBD in COPD patients.…”
Section: Biochemistry Of the Associationmentioning
confidence: 99%
“…Airway diseases are one of the most commonly studied manifestations of IBD [5]. Concurrently, the risk of new-onset IBD is found to be higher in populations with obstructive pulmonary diseases such as obstructive pulmonary disease (COPD), asthma, and bronchiectasis compared to the general population without these conditions [6,7,8]. This newly documented evidence of IBD incidence among patients with pulmonary diseases and the higher than the estimated prevalence of pulmonary conditions among IBD patients support the hypothesis of a two-way association [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations